발목 골절에서 관절경의 역할 - 김갑래; 한승환; 박광환; 김대유; 임경훈; 이성현; Gab-Lae Kim; Seung Hwan Han; Kwang Hwan Park; Dae-Yoo Kim; Gyeong Hoon Lim; Sung Hyun Lee (대한족부족관절학회지, 2025)
The fundamental principles for treating ankle fractures, as with other intra-articular fractures, are anatomical reduction and stable internal fixation. Despite successful reduction, between 14% and 40% of patients continue to experience persistent pain or unsatisfactory functional outcomes. Furthermore, approximately 1% of patients progress to post-traumatic arthritis, necessitating further surgical intervention. Ankle fractures are frequently accompanied by intra-articular injuries, including osteochondral lesions, ligament tears, and syndesmosis injuries. Arthroscopy is becoming increasingly prevalent in managing acute ankle fractures by assessing intra-articular damage and facilitating accurate reduction. This review examined the role and indications for arthroscopy in ankle fractures, particularly emphasizing its benefits in diagnosing and managing associated injuries, including osteochondral lesions, syndesmosis, and deltoid ligament injuries. Furthermore, arthroscopy facilitates fracture reduction, offering a minimally invasive approach with a shorter recovery period and enhanced visualization. Its use extends to pediatric fractures and complex cases such as Maisonneuve and calcaneal fractures, potentially improving outcomes while minimizing complications. Understanding the evolving indications and benefits of arthroscopy for ankle fractures can lead to improved clinical outcomes and reduced complications.